The Influence of Leadership Style and Work Discipline on the Performance of PNS Teachers in Public Junior High Schools in Banyuasin I District - Amirudin; Syaiful Eddy; Reva Maria (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
This study aims to analyze the influence of principal leadership style and work discipline on the performance of civil servant (PNS) teachers at public junior high schools in Banyuasin I District. This study employed a quantitative approach using an ex post facto survey design involving all 83 civil servant teachers through a saturated sampling technique. Data were collected using questionnaires and documentation and analyzed using descriptive statistics, simple linear regression, multiple linear regression, t-tests, F-tests, and the coefficient of determination with IBM SPSS Statistics Version 26. The findings indicate that principal leadership style has a positive and significant effect on teacher performance, while work discipline also positively and significantly influences teacher performance. Simultaneously, both variables significantly contribute to improving teacher performance. The coefficient of determination shows that teacher performance is influenced by leadership style and work discipline, whereas the remaining variance is explained by other organizational factors. This study contributes to educational management by providing empirical evidence that strengthening instructional leadership and fostering work discipline are strategic approaches to improving teacher performance in public junior high schools.